Effectiveness of the Exogegenous and Endogenous Variables as Determinants of Money Supply in Nigeria: 1980-2019. (Global Journal of Management and Business Research, 2021)
This work dealt on the effectiveness of the exogenous and endogenous variables as determinants of money supply in Nigeria. It is a contribution to the existing debate on money supply exogeniety/endogeneity concepts. To examine these issues, this work adopted two models and used annual time-series data for the period 1980 to 2019. It employed the ordinary least square (OLS) technique, the unit root test, the Johansson co-integration procedure and the error correction mechanism (ECM) to analyse the data. Most variables in the models were significant and rightly signed. From the exogenous model, Treasury Bill Rate (TBR), Monetary Policy rate (MPR) and Liquidity ratio (LQ) significantly impacted to changes in money supply in the short run. But in the long run analysis only TBR was found to be significant and impacted positively to changes in money supply. The result indicated a low coefficient of determination (R2) and weak disequilibrium adjustment value (in the long run) depicting weak exogeniety and less effective.